Computed Tomography Study of the Retrosigmoid Craniotomy Keyhole Approach Using Surface Landmarks - Wei Hu; Jiang Zhou; Zheng-Min Liu; Ye Li; Qing-Feng Cai; Xiao-Ming Hu; Yan-Bing Yu (International Journal of Clinical Practice)
Background. Due to a lack of accessibility and individual differences in surgical procedures, many previous studies on keyholes are not practical. Objective. To study the surface landmarks for optimal keyhole placement in the retrosigmoid approach. Methods. The three-dimensional (3D) skull images of 79 patients were reconstructed using workstations, with a total of 149 hemiskull base 3D images then analyzed. Skull-surface landmarks were marked, the lateral-skull surface was observed, and the positional relationships between the asterion and the extension line of the posterior margin of the mastoid process were measured. The position of the superior curvature of the sigmoid sinus groove was located before it was projected onto the lateral surface of the skull and defined as the keypoint. The positional relationship between the keypoint and the skull-surface landmarks was observed in an established coordinate system using spatial proportion relationships. Results. The asterion was located around the extension line of the posterior margin of the mastoid process, and the vertical distance from the extension line was <15 mm. It was found that 93.29% (139/149) of the keypoints were located in a 7 mm radius circle, with the center at (−0.41, −3.01) in the coordinate system in the 3D computed tomography images. Conclusion. When using this method, the spatial proportion relationship of the anatomical marks can accurately locate keyholes, therefore providing technical support when employing the retrosigmoid approach.